Characterization and Pathogenicity of Rhizoctonia solani Kühn Associated with Sheath Blight in Local Rice Varieties (Oryza sativa L.) of Special Region of Yogyakarta - Maulin Nafisa; Adiana Nayogyani; Rina Sri Kasiamdari (Jurnal Perlindungan Tanaman Indonesia, 2021)
In Indonesia, rice is used as the first strategic and priority food commodity in agricultural development. However, in practice, efforts to increase it still experience various obstacles, one of which is caused by the attack of pathogen Rhizoctonia solani. This study aimed to determine the characters of R. solani and observe its pathogenicity on some local rice varieties in the Special Region of Yogyakarta. Four isolates of R. solani were used, namely RS MS2, RS MKP2, RS UMB, and RS PN, as well as six varieties of local rice varieties, which were Menthik Susu, Cempo Merah, Cempo Hitam, Segreng, Menoreh, and Hitam Makaryo, and national rice varieties IR 64 and Ciherang. Morphological characterization was carried out based on the cultural characteristics of the colony, hyphae, and sclerotia. A pathogenicity test was carried out using the Detached Leaf Inoculation method. The result showed that R. solani characters vary from whitish-brown, yellowish-brown, and light brown colonies; moderate and fast growth rates; abundant-aerial, moderate-aerial, and slight-aerial growth patterns; 90° hyphae branching, narrowing of hyphae at the branching point, and presence of sclerotia. The pathogenicity test gave the results of all isolates having varying pathogenicity levels on each rice variety. Menthik Susu, Cempo Hitam, and Hitam Makaryo were resistant to R. solani. Cempo Merah and Segreng were considered as moderately resistant varieties, whereas Menoreh was categorized as moderately susceptible. Ciherang and IR64 were susceptible varieties to R. solani.